Do Local Government Executives Believe They Are More Political or Administrative? An Analysis of the Ethics of Administrative Officer Self-Perception. (4th July 2018) - Potter, Michael; Eskridge, Robert
Abstract : This research focuses on the self-perceptions of managers in medium-sized localities. Using a survey of 249 mayors, chief administrative officers, and city managers the authors gathered data regarding the tasks these executives perceive themselves as performing. Using time allocation and function allocation models, the authors then searched for links between job titles and rates of administrative or political functions. The analysis finds that mayors allocate their time in more political areas, while city managers and chief administrative officers spend more of their time in administrative/managerial areas. While there was little difference in functional activity, self-perception between appointed chief administrative officers and city managers, mayors saw their functional role largely as managerial and political. The higher rate of managerial self-perception for mayors could lead to a lack of deference to the expertise of appointed chief administrative officers and city managers. The article theorizes that administrative and political management should not be treated as separate skill sets but should be interchangeable based on context.